POPULATION STRUCTURE AND LINKAGE DISEQUILIBRIUM ASSESSMENT AMONG COTTON VARIETIES FROM TWO IMPORTANT COTTON GROWING REGIONS IN PUNJAB, PAKISTAN - M. Saeed1; S. Akram; M. Azeem; X. Song2; X. Sun; M. Riaz (Journal of Animal and Plant Sciences, 2020)
Cotton (Gossypium hirsutum L.) is an important crop worldwide cultivated for natural fiber and vegetable oil purposes. Artificial selection for pyramiding desirable traits in cotton varieties has a great influence on molecular evolution of cotton genome and species. Population structure and linkage disequilibrium (LD) are two important attributes that shed light on the underlying molecular evolution and genetic diversity of a plant species cultivated in a particular ecological region. In this study, population structure and linkage disequilibrium were assessed among 25 cotton cultivars from two important ecological regions (Central Punjab and South Punjab) in Pakistan. The 25 cultivars were genotyped with 92 primer pairs of simple sequence repeats (SSR) markers. Population structure was assessed by STRUCTURE 2.0 software. Linkage disequilibrium was assessed by TASSEL 2.1 software. The STRUCTURE analysis revealed three subpopulations. Sixty-six pairs of loci (0.83%) showed a significant LD (P ≤ 0.001, r2 > 0.1). At P ≤ 0.001, three LD haplotypic blocks were identified on chr. 11 (A11), 16 (D7), and 23 (D9), indicating that artificial selection has had a strong influence on the molecular evolution of cotton crop in a specific ecological region.
Keywords: Artificial selection; Cotton; Ecological region; Linkage disequilibrium; Molecular evolution; Population structure